1997
DOI: 10.1172/jci119597
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction of the antiatherogenic effect of estrogen by long-term inhibition of nitric oxide synthesis in cholesterol-clamped rabbits.

Abstract: The purpose of this study was to investigate whether endothelium-derived nitric oxide (NO) is involved in the plasma lipid-independent antiatherogenic effect of estrogen and levormeloxifene, a partial estrogen receptor agonist. 85 rabbits were ovariectomized and balloon-injured in the middle thoracic aorta. The rabbits were fed a cholesterol-enriched diet supplemented with 17 ␤ -estradiol, levormeloxifene, or placebo, either alone, or together with 160 g/ml N G -nitro-L -arginine methyl ester ( L -NAME), an NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…29,30 The difference between our results and previous reports may be due to the following reasons. We did not clamp the plasma cholesterol level, which may have had some additional effects, although these levels did not show any statistically significant differences.…”
Section: Hayashi Et Alcontrasting
confidence: 88%
See 1 more Smart Citation
“…29,30 The difference between our results and previous reports may be due to the following reasons. We did not clamp the plasma cholesterol level, which may have had some additional effects, although these levels did not show any statistically significant differences.…”
Section: Hayashi Et Alcontrasting
confidence: 88%
“…10,11 Furthermore, this assumption is supported by a recent study, which showed that inhibition of NOS reduced the antiatherosclerotic effect of estrogen in cholesterol diet-induced atherosclerosis in the rabbit aorta. 34 However, we must consider another possibility that improved endothelial function due to estrogen treatment was not only the cause of the antiatherosclerotic effect but also the result of diminished atherosclerotic lesion formation through mechanisms other than NO. Some reports have described that the effects of estrogen are not through NO but through their dependence on another system and have concluded that NO does not play a role in some types of atherosclerosis.…”
Section: Hayashi Et Almentioning
confidence: 99%
“…Somewhat unexpectedly, increasing NO bioavailability in ovariectomized Apoe KO mice failed to affect development of fatty streaks, suggesting that prevention of early atherosclerosis by E 2 is independent of NO production (Elhage et al 1997b, Hodgin et al 2002. However, chronic induction of endothelial dysfunction by prolonged administration of NOS inhibitor aggravated atherosclerosis and specifically abolished atheroprotective effects of E 2 in intact but not in de-endothelialized aorta in female rabbits on a hypercholesterolemic diet (Holm et al 1997). In addition, a close inverse correlation between NO production and the arterial lesion extent was observed in rabbits under the condition of severe hypercholesterolemia combined with or without endothelial dysfunction (Nascimento et al 1999, Hayashi et al 2000.…”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 92%
“…The central role of endothelium for the atheroprotective effects of estrogens was initially suggested by Holm et al (1997), who demonstrated complete loss of anti-atherogenic effects of estrogens in hypercholesterolemic rabbits after destructing the endothelial layer in the aorta using a balloon catheter. However, the ultimate proof for the obligatory involvement of endothelial cells in the estrogen-exerted atheroprotection in animal models was provided by Billon-Galés et al (2009a).…”
Section: Mechanisms Underlying Anti-atherogenic Effects Of Estrogens mentioning
confidence: 99%
“…29,30 More recently, direct evidence was shown that NO mediates the antiatherosclerotic effect of estrogen. 31 DHEA is known to convert to estradiol in vivo. Therefore, the current study was undertaken to determine whether the antiatherosclerotic effect of DHEA is related to its conversion to estrogen and to define the role of NO in the antiatherosclerotic effect of DHEA.…”
mentioning
confidence: 99%